2017
DOI: 10.1371/journal.pone.0186348
|View full text |Cite
|
Sign up to set email alerts
|

Urbanity as a determinant of exposure to grass pollen in Helsinki Metropolitan area, Finland

Abstract: Little is known about the levels of exposure to grass pollen in urban environments. We assessed the spatio-temporal variation of grass pollen concentrations and the role of urbanity as a determinant of grass pollen exposure in the Helsinki Metropolitan area. We monitored grass pollen concentrations in 2013 at 16 sites during the peak pollen season by using rotorod-type samplers at the breathing height. The sites were in the cities of Helsinki and Espoo, Finland, and formed city-specific lines that represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…Although it has been suggested that different types of pollen sampling can be used to get a rough estimate of pollen exposure,47 many of the approaches may not have captured the daily individual exposures at the breathing level in satisfactory detail. In 2013, we monitored grass pollen concentrations at 16 sites in the cities of Helsinki and Espoo during the peak pollen season by using rotorod-type samplers at the breathing height 48. We identified substantial variation in exposure concentrations at breathing height according to urbanity of the site and time of the day within areas covered by our roof level monitoring stations.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been suggested that different types of pollen sampling can be used to get a rough estimate of pollen exposure,47 many of the approaches may not have captured the daily individual exposures at the breathing level in satisfactory detail. In 2013, we monitored grass pollen concentrations at 16 sites in the cities of Helsinki and Espoo during the peak pollen season by using rotorod-type samplers at the breathing height 48. We identified substantial variation in exposure concentrations at breathing height according to urbanity of the site and time of the day within areas covered by our roof level monitoring stations.…”
Section: Resultsmentioning
confidence: 99%
“…When considering a 1-km ring around the pollen traps ( Figure 5), the surface of urban green zones around the pollen monitoring station DEBIED (30% of the total) was greater than the surface around DEMUNC (15% of the total). Furthermore, the surface of surrounding urbanized areas was greater for the DEMUNC pollen trap, which implies lower amounts of pollen [42]. This could be the explanation for the significant differences for the pollen amounts from woody taxa such as Cupressaceae/Taxaceae and Carpinus.…”
Section: Abundance Of the Pollen Types In The Airmentioning
confidence: 96%
“…However, these anemophilous trees are also commonly found in forested areas surrounding Central European cities and as such it is likely that the majority of airborne pollen from these species recorded in Munich come from outside of the city [44,45]. It has also been shown that different levels of urbanization lead to differences in airborne pollen levels, with the lowest pollen concentrations generally registered in the most urban sites following an urban-rural gradient [42,46,47]. A better knowledge of this effect could be achieved by studying the local vegetation around the pollen traps in Munich in a more detailed way [12,48].…”
Section: Abundance Of the Pollen Types In The Airmentioning
confidence: 99%
“…Global warming has resulted in longer pollen seasons, changes in crop patterns, and pollen distribution patterns [33]. Environmental conditions specific to urban regions such as high nocturnal temperatures, increased atmospheric carbon dioxide, and nitrogen deposition provide favourable conditions for agriculture, leading to increased production of pollen and airborne allergenic protein loads [51-54]. Furthermore, airborne pollutants interact with aeroallergens, enhancing airway permeability and allergen penetration, which compound their detrimental effects on asthma exacerbations [55].…”
Section: First-generation International Immigrantsmentioning
confidence: 99%